If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7ln(x + 5) + -9ln(x) = 0 Reorder the terms: 7ln(5 + x) + -9ln(x) = 0 (5 * 7ln + x * 7ln) + -9ln(x) = 0 (35ln + 7lnx) + -9ln(x) = 0 Multiply ln * x 35ln + 7lnx + -9lnx = 0 Combine like terms: 7lnx + -9lnx = -2lnx 35ln + -2lnx = 0 Solving 35ln + -2lnx = 0 Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Factor out the Greatest Common Factor (GCF), 'ln'. ln(35 + -2x) = 0Subproblem 1
Set the factor 'ln' equal to zero and attempt to solve: Simplifying ln = 0 Solving ln = 0 Move all terms containing l to the left, all other terms to the right. Simplifying ln = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(35 + -2x)' equal to zero and attempt to solve: Simplifying 35 + -2x = 0 Solving 35 + -2x = 0 Move all terms containing l to the left, all other terms to the right. Add '-35' to each side of the equation. 35 + -35 + -2x = 0 + -35 Combine like terms: 35 + -35 = 0 0 + -2x = 0 + -35 -2x = 0 + -35 Combine like terms: 0 + -35 = -35 -2x = -35 Add '2x' to each side of the equation. -2x + 2x = -35 + 2x Combine like terms: -2x + 2x = 0 0 = -35 + 2x Simplifying 0 = -35 + 2x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 8x+8(-5+3x)=5 | | (h+9)=2(h+9)+-6 | | 2(x-3)+x+4=9-2x+1+x | | M^2+7m+p^2=0 | | y(h+9)=2(h+9)+-6 | | 2x-34=20 | | 2t^3+t-3=0 | | m+m+9=3+m | | 21=-5k | | M^2+7m=p^2 | | 20x-5+17-3x= | | 21=-5+k | | 70+70+w*2=340 | | 5x+3-37=6x+23-8x | | -4x+-2.363636364=-2 | | 12=44x-12 | | 0.5+0.25y-3y=7 | | 0.5cos(x)=sin(2x) | | Y=1.1x^2+4.2x+4.9 | | 2x^2+x=69 | | y-4.5=12.2 | | x^2+(y-5)=30 | | 4x^2(-5+-15x+x^2+3x^3)= | | 8.1=a-(-2.4) | | 0.3x^2-2x+3.6=0 | | -5x+7=-8+9x | | 42u=4.66666666667 | | -6x-3=4x+7 | | 50=10x+15-3x | | g+-7=21 | | 2x(3)-18x=0 | | (3x+6)(2x-5)=0 |